Impact of personality and gender diversity on software development teams' performance - Gila, A.R. (Institute of Electrical and Electronics Engineers Inc., 2014)
Human aspect is considered as one of the success factors for software development. Besides, diversity is labeled as the most effective element for creating effectiveness in team performance. Thus, this study has aimed to find the effects of gender diversity on team performance based on personality types. The personality types' variations were found effective on team performance based on genders. For instance, male-lead groups were found convenient with both genders but female-lead groups looked much comfortable with only female members. Moreover, female-gender looked uneasy in male dominant teams especially when their personality is E (extrovert). Whereas, male-gender was observed as digestible in female-lead teams if the I (introvert) personality is dominating. Â© 2014 IEEE.